A Tale of the Unknown Unknowns A Mesolithic Pit Alignment and a Neolithic Timber Hall at Warren Field, Crathes, Aberdeenshire - Murray, Hilary K. (Oxbow Books, 2009)
The site of Warren Field in Scotland revealed two unusual and enigmatic features; an alignment of pits and a large, rectangular feature interpreted as a timber building. Excavations confirmed that the timber structure was an early Neolithic building and that the pits had been in use from the Mesolithic. This report details the excavations and reveals that the hall was associated with the storage and or consumption of cereals, including bread wheat, and pollen evidence suggests that the hall may have been part of a larger area of activity involving cereal cultivation and processing. The pits are fully documented and environmental evidence sheds light on the surrounding landscape.